SCIENTIFIC APPROACH OF 2013 CURRICULUM: TEACHERS' IMPLEMENTATION IN ENGLISH LANGUAGE TEACHING : a case study of seventh grade teachers in a state junior high school in Bandung - Ratnaningsih, Sri (2017)
The research is aimed at investigating the teachers' implementation of scientific approach in English Language Teaching in one state junior high school in Bandung Regency. In addition, this research discusses the conformation of the scientific approach implementation and the lesson plan based on the 2013 curriculum. This research employs a case study-qualitative research design. The data were obtained from classroom observation, teachers' lesson plan analysis and interview. The findings present that the teachers implemented the scientific stages in English Language Teaching. They conduct observing, questioning, experimenting, associating and communicating in the sequence activities. Besides, the teachers can demonstrate the student-centered which is strengthen by collaborative, cooperative, active and meaningful learning. However, in the conformation of the implementation with lesson plan, based on the indicators, learning objectives, learning material, learning media, scientific stages and scientific approach model (discovery learning, inquiry learning, problem based learning and project based learning), the teachers have to underline and mention the scientific approach model and state learning objectives. More than that, the other components have been presented well in both teaching and lesson plan